Parallel Calculation of Random Vibration for Reentry Vehicles in Fluctuating Pressure Environment - Xuanhua Fan; Jun Liang; Keying Wang; Huan Zhou (Shock and Vibration)
The reentry vehicle is in an unconstrained free-flight state during the reentry process. The pressure of air fluctuations acts on the external surface of the vehicle and induces a random vibration environment with a wide-frequency range, which makes great influences on the structural dynamic properties of vehicles. This paper aims at the parallel calculation of the wide-frequency random vibration problems for the free body under multipoint fluctuating pressure loads. The calculation method is based on the self-developed JAUMIN framework and PANDA platform. The novel algorithm based on the modal superposition method reduces the computational complexity, realizes the parallel calculation, and achieves the maximum numerical simulation calculation capacity of 1.045 billion degrees of freedom (DOFs) while improving the calculation efficiency and the accuracy of the results. Finally, this article also uses typical examples to verify the correctness and parallel scalability of algorithms and programs.